Transcranial Magnetic Stimulation of Medial Prefrontal and Cingulate Cortices Reduces Cocaine Self-Administration: A Pilot Study - Martinez, Diana; Urban, Nina; Grassetti, Alex; Chang, Dinissa; Hu, Mei-Chen; Zangen, Abraham; Levin, Frances R.; Foltin, Richard; Nunes, Edward V. (Frontiers in Psychiatry, 2018)
Background: Previous studies have shown that repetitive transcranial magnetic stimulation (rTMS) to the dorsolateral prefrontal cortex may serve as a potential treatment for cocaine use disorder (CUD), which remains a public healthy problem that is refractory to treatment. The goal of this pilot study was to investigate the effect of rTMS on cocaine self-administration in the laboratory. In the self-administration sessions, CUD participants chose between cocaine and an alternative reinforcer (money) in order to directly measure cocaine-seeking behavior. The rTMS was delivered with the H7 coil, which provides stimulation to the medial prefrontal cortex (mPFC) and anterior cingulate cortex (ACC). These brain regions were targeted based on previous imaging studies demonstrating alterations in their activation and connectivity in CUD. Methods: Volunteers with CUD were admitted to an inpatient unit for the entire study and assigned to one of three rTMS groups: high frequency (10 Hz), low frequency (1 Hz), and sham. Six participants were included in each group and the rTMS was delivered on weekdays for three weeks. The cocaine self-administration sessions were performed at three time points: at baseline (pre-TMS, session 1), after 4 days of rTMS (session 2), and after 13 days of rTMS (session 3). During each self-administration session, participants outcome measure was the number of choices for cocaine. Results: The results showed a significant group by time effect (p = .02), where the choices for cocaine decreased between sessions 2 and 3 in the high frequency group. There was no effect of rTMS on cocaine self-administration the low frequency or sham groups. Conclusion: Taken in the context of the existing literature, these results contribute to the data showing that high frequency rTMS to the prefrontal cortex may serve as a potential treatment for CUD. □